Policy Implementation of the Online Single Submission (OSS) System in Enhancing Licensing Service Delivery at the Investment and One-Stop Integrated Services Office of East Java Province - Anastasya Sibarani Tasya (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Online Single Submission (OSS) is a web-based business licensing system developed to simplify licensing procedures and improve the quality of public services in the investment sector. This study aims to analyze the implementation of the OSS policy at the Investment and One-Stop Integrated Services Office (DPMPTSP) of East Java Province. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation, which were analyzed using data triangulation techniques. The findings indicate that the implementation of OSS in East Java Province has been relatively effective, particularly in improving the efficiency of licensing processes and supporting the increase in regional investment realization. Nevertheless, several challenges remain, including limited human resources, technical readiness of the system, and business actors’ understanding of OSS mechanisms. Therefore, strengthening the capacity of government officials, optimizing information technology systems, and conducting continuous socialization are necessary to support the optimal implementation of OSS at the regional level.